Upaya Meningkatkan Rasa Ingin Tahu Dan Pemahaman Sebab Akibat Anak Usia Dini Melalui Eksperimen Pencampuran Warna - Rostiyah Rostiyah; Abdul Azis; Desi Suryani (Institut Madani Nusantara, 2025)
Early childhood curiosity is a natural trait characterized by a strong interest in the surrounding environment, which encourages them to ask questions, explore, and learn new things. Curiosity is crucial for children's cognitive, language, and problem-solving development. Understanding cause and effect in early childhood is the child's ability to understand that every action (cause) will produce a reaction or consequence (result), which begins in the immediate environment, then develops over time through exploration and play. Classroom Action Research was conducted to increase curiosity and understanding of cause and effect in early childhood Group B (5-6 years) at the Melati Early Childhood Education Post through the application of the color mixing experiment method. The background of this study was the low initiative of children in asking questions and the lack of logical ability in connecting an event with its outcome (cause and effect). The research subjects were 10 children in group B. The data collection instruments were observation sheets of children's activities and observation sheets of teachers' abilities. The pre-cycle results showed that the level of achievement of children's curiosity and understanding of cause and effect was in the poor category. After the implementation of the actions in Cycle I and Cycle II, there was a significant increase. At the end of Cycle II, the percentage of children's curiosity and understanding of cause and effect indicators reached 80%, exceeding the success indicator set at 75%. This indicates that the color mixing experiment method is effective in increasing curiosity and understanding of cause and effect in early childhood.